Structural and functional deficits and couplings in severe and moderate OCD. (April 2023) - Xu, Yinhuan; Zheng, Ruiping; Guo, Huirong; Wei, Yarui; Wen, Baohong; Dai, Shufan; Han, Shaoqiang; Cheng, Jingliang; Zhang, Yan
Abstract: Changes in gray matter volume and functional connections have been frequently observed in patients with obsessive compulsive disorder. However, different grouping may cause diverse volume alterations and could draw more adverse conclusions about the pathophysiology of obsessive compulsive disorder(OCD). Most of them preferred to divide subjects into patients and healthy controls, rather than a detailed subgroup. Moreover, multimodal neuroimaging studies about structural-functional defects and couplings are rather rare. Our aim was to explore gray matter volume(GMV) and functional networks abnormalities induced by structural deficits based on severity of Yale-Brown Obsessive Compulsive Scale(Y-BOCS) symptom including OCD patients with severe(S-OCD, n = 31) and moderate symptoms(M-OCD, n = 42) and healthy controls (HCs, n = 54); Voxel-based morphometry(VBM) method was used to detect GMV differences among three groups, then used as masks according to one-way analysis of variance(ANOVA) results for the subsequent resting-state functional connectivity(rs-FC) analysis. Besides, correlation and subgroup analysis were performed to detect the potential roles of structural deficits between every two groups. ANOVA analysis showed that both S-OCD and M-OCD had increased volume in anterior cingulate cortex(ACC), left precuneus(L-Pre) and paracentral lobule(PCL), postcentral gyrus, left inferior occipital gyrus(L-IOG) and right superior occipital gyrus(R-SOG) and bilateral cuneus, middle occipital gyrus(MOG), and calcarine. Additionally, increased connections between Pre and angular gyrus(AG) and inferior parietal lobule(IPL) have been found. Moreover, connections between the left cuneus and lingual gyrus, between IOG and left lingual gyrus, fusiform and between L-MOG and cerebellum were also included. Subgroup analysis showed that decreased GMV in left caudate was negatively correlated with compulsion and total score in patients with moderate symptom compared to HCs. Our findings indicated that altered GMV in occipital-related regions, Pre, ACC and PCL and the disrupted FC networks including MOG-cerebellum and Pre-AG and IPL. Moreover, subgroup GMV analysis furtherly revealed negative associations between GMV changes and Y-BOCS symptom, offering preparatory proof for the involvement of structural and functional deficits in cortical-subcortical circuitry. Thus, they could provide insights into the neurobiological basis.